2023
DOI: 10.5114/wiitm.2023.128713
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transversus abdominis plane block combined with low-dose dexmedetomidine on elderly patients undergoing laparoscopic colectomy.

Abstract: Introduction Colon cancer is a common malignancy, for which surgery is currently the preferred therapy. Aim To assess the effect of transversus abdominis plane block (TAPB) combined with low-dose dexmedetomidine on elderly patients undergoing laparoscopic colectomy. Material and methods Sixty-two elderly patients undergoing laparoscopic colectomy between March 2021 and March 2022 were randomly selected and equally divided into Group A (low-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…However, the underlying mechanism of POCD remains unknown. Previous studies suggested that the analgesic properties of DEX could be triggered by several mechanisms, including transversus intrathecal and abdominis plane block ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying mechanism of POCD remains unknown. Previous studies suggested that the analgesic properties of DEX could be triggered by several mechanisms, including transversus intrathecal and abdominis plane block ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%